Foreign Aid and Industrial Development in Pakistan - Breacher, Irving (Cambridge ; University Press, 1972)
Study of the effects of economic aid on industrial development in Pakistan - covers theoretical aspects, aid flows during the period from 1950 to 1968, interaction with economic growth and national planning, balance of payments and external indebtedness, the role of developed countries (incl. The role of socialist countries) and international organizations, commodity aid and its impact on economic development and industrialization, etc., and includes case studies of public sector and private sector development projects. Bibliography and statistical tables
Keywords: Economic assistance Pakistan; developement industrial; Pakistan Economic development Foreign assistance